A Case Report Total Intravenous Anesthesia Combined with Peribulbar Block in Vitrectomy Operation with Heart Disorder - Lubis, Andriamuri Primaputra; Lubis, Adhika Syaputra (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2022)
Introduction: Vitrectomy is eye surgery to evaluate the retina by removing the vitreous gel which is principally carried out in three stages, namely retinal detachment repair, membrane peeling, and crystalline lens. In this operation, the anesthetic technique that needs to be emphasized is not increasing intraocular pressure and avoiding the oculocardiac reflex. This operation can be performed with a peribulbar or retrobulbar block, however, total intravenous anesthesia may also be considered in patients with other comorbidities.Case Presentation: Male, 55 years old, 96 kgs, with the chief complaint of blurred vision in the last 3 weeks ago. There were no other complaints but the patient has a history of hypertension, diabetes mellitus type II, congestive heart failure with a history of mitral valve replacement (MVR), and permanent pacemaker (PPM) usage from 2015. The patient had a history of warfarin and novamox usage 7 days ago. From the exam, the patient was diagnosed with ablatio retina + post-MVR and scheduled to have a vitrectomy. The patient was positioned supine with 300 heads up. The patient was given 3 liters of oxygen via nasal cannula, premedicated with fentanyl 50 mcg, then induced with propofol 100 mg bolus intravenously until sleep nonapnea before continuing with continuous propofol via syringe pump. The patient was maintained by propofol 0.5 mg/kg BW/hour. Next, the patient was given a peribulbar block with 2mL Lidocaine 2% and 2mL Bupivacaine 0.5%. During operation, there was no significant hemodynamic fluctuation until finished. Conclusion: The patient thus will undergo vitrectomy can be performed with peripheral nerve blocks such as retrobulbar anesthesia or peribulbar anesthesia. However, after knowing about the patient’s medical history, in this case, with a history of cardiac events and also undergone open-heart surgery, total intravenous anesthesia combined with a peribulbar block was considered the most suitable technique.